EP4 receptor stimulation in combination with core decompression therapy enhanced bone regeneration in a canine model of osteonecrosis of femoral head - Hirano, Kyoko; Miyagawa, Takaki; Nishida, Masahiro; Akiyama, Haruhiko (Frontiers in Bioengineering and Biotechnology, 2025)
Core decompression (CD) is a minimally invasive procedure widely used to treat early-stage osteonecrosis of the femoral head (ONFH). However, CD alone often yields suboptimal outcomes in promoting bone regeneration in necrotic lesions, highlighting the need for novel therapeutic approaches. In this study, we evaluated the combined effects of CD surgery and local administration of AKDS001, a small-molecule EP4 receptor agonist, in a canine ONFH model. AKDS001 was incorporated into biocompatible, biodegradable polylactic-coglycolic acid microspheres (AKDS001 MSs) for sustained local drug release. The bone-regenerative effects of local administration of AKDS001 MSs combined with CD surgery were evaluated in intact canines or a canine ONFH model, induced by ethanol injection into the femoral head. Safety and local tolerability of the therapy was also investigated in the model. AKDS001 MSs enhanced bone formation in intact dog femurs compared to CD only or MSs without AKDS001. In the ONFH model, CD alone resulted in limited bone repair at 12 weeks postsurgery. In contrast, compared with CD alone, the combination of AKDS001 MSs and CD dose-dependently increased the bone volume, bone mineral density, and tissue mineral density in the CD tunnel. Histological analyses further revealed significant amelioration of the necrotic lesions. Importantly, no systemic or local adverse effects were observed. In conclusion, local administration of AKDS001 MSs combined with CD surgery significantly enhanced bone regeneration in necrotic lesions in a canine ONFH model, demonstrating both efficacy and favorable safety with local tolerability.